Fredrika Bremer correspondence - Bremer, Fredrika, 1801-1865.
Letter from Bremer to Elizabeth Palmer Peabody discussing her travel plans and her intention to visit Elizabeth, Nathaniel Hawthorne, and Sophia Peabody Hawthorne during the summer of 1850. Bremer also mentions having seen Horace Mann.
Author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Published in Fredrika Bremers brev; samlade och utg. av Klara Johanson och Ellen Kleman (Stockholm: P.A. Norstedt & Soners Forlag, 1920).
Keywords: Bremer, Fredrika, -- 1801-1865 -- Travel; Hawthorne, Nathaniel, -- 1804-1864.; Hawthorne, Sophia Peabody, -- 1809-1871.; Mann, Horace, -- 1796-1859.; Peabody, Elizabeth Palmer, -- 1804-1894 -- Correspondence; Voyages and travels; Authors